The Effects of Foods on Blood Lipids in Non-alcoholic Fatty Liver Disease (NAFLD)—A Systematic Review and Meta-Analysis - Rosqvist, Fredrik; Rydell, Andreas; Iggman, David (Frontiers in Nutrition, 2020)
Background: Non-alcoholic fatty liver disease (NAFLD) is associated with dyslipidemia and increased cardiovascular disease risk. Dietary choices may produce profound effects on blood lipids. Thus, the purpose of this study was to investigate which foods modify blood lipids in NAFLD. Methods: Systematic review of published systematic reviews and randomized controlled trials (RCTs). Searches were performed in PubMed, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials, from inception through March 2020. Studies in populations with NAFLD, which provided data on foods or dietary patterns and blood lipids were included, but not weight loss diets, supplements, nor individual nutrients. The strength of evidence was evaluated using The Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Results: No relevant systematic reviews were identified. Eleven RCTs were included in the qualitative synthesis. Two RCTs were included in meta-analyses, regarding the comparison between Mediterranean and Low-fat diets, in which there were no clear effects on either high-density lipoprotein cholesterol or triglycerides, with Low evidence. From single RCTs, there was Moderate evidence for reduced triglycerides by a healthy dietary pattern, compared with usual care; and for reduced total cholesterol by a probiotic yogurt, enriched with Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12, compared with conventional yogurt. For all other comparisons, the evidence was considered as Low or Very low. Conclusion: Few studies were identified which reported effects of foods on blood lipids in subjects with NAFLD. The possible beneficial effect of probiotics warrants further study. PROSPERO identifier: CRD42020178927.